The Potential of Mystification in The Jakarta Post Articles toward Human Right Violation Issue - Fitriyani, Vita Muflihah (Universitas Ahmad Dahlan, 2025)
This paper tries to unfold the potential of mystification in the Jakarta Post Articles toward human right violation issues during 2014 and 2023. This study focuses on nominalization and passivization. The method of this study is the identification of mystifying and non-mystifying texts in passives based on Lingle's (2023) framework criteria. It aims to find whether the agent or patient (Hart 2021) is potentially mystified by passivization (Langacker 2008) or nominalizations (Fairclough 2003; Halliday & Matthiessen 1999). The results suggest that the agent is the most potential mystified in articles for 2014 and 2023. Agents are potentially mystified by nominalizations such as killing, kidnapping, death, disappearance, massacre, and atrocities. Meanwhile, the patient is potentially mystified by its impact, for example, insubordination, violators, and cases, also through the impersonality. The dismissing agency in nominalization means that the writer tries to reduce the information. Besides, reifying verbs to nouns indicates the existence of such entities.